Volume 5B: Heat Transfer 2015
DOI: 10.1115/gt2015-42771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crossflow in an Internal-Cooling Channel on Film Cooling of a Flat Plate Through Compound-Angle Holes

Abstract: CFD simulations were performed to study the film cooling of a flat plate from one row of compound-angles holes fed by an internal-cooling passage that is perpendicular to the hot-gas flow. Parameters examined include direction of flow in the internal cooling passage and blowing ratios of 0.5, 1.0, and 1.5 with the coolant-to-hot-gas density ratio kept at 1.5. This CFD study is based on steady RANS with the shear-stress transport (SST) and realizable k-ε turbulence models. To understand the effects of unsteadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Zhang et al [11] experimentally studied the effects of vortex generator height (H/D) and location (L/D) on the film cooling effectiveness of flat plate, and found that the vortex generator contributes to enhancing film cooling effect. and Stratton et al [14] studied the effect of the direction of internal crossflow on the film cooling effectiveness of two perpendicular flat plate channels connected by a row of different shaped film holes by experimental method and CFD simulations, and found that LES is able to predict adiabatic film cooling effectiveness with reasonable accuracy. The above research shows that film cooling technology has been extensively studied, but the influence of the internal cooling structure of the internal cooling channel on the film cooling efficiency is neglected, so that the film cooling characteristics are underestimated or overvalued.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] experimentally studied the effects of vortex generator height (H/D) and location (L/D) on the film cooling effectiveness of flat plate, and found that the vortex generator contributes to enhancing film cooling effect. and Stratton et al [14] studied the effect of the direction of internal crossflow on the film cooling effectiveness of two perpendicular flat plate channels connected by a row of different shaped film holes by experimental method and CFD simulations, and found that LES is able to predict adiabatic film cooling effectiveness with reasonable accuracy. The above research shows that film cooling technology has been extensively studied, but the influence of the internal cooling structure of the internal cooling channel on the film cooling efficiency is neglected, so that the film cooling characteristics are underestimated or overvalued.…”
Section: Introductionmentioning
confidence: 99%
“…Acharya's research (Acharya, 2013) found that the best film effectiveness could be obtained by making the cooling flow direction consistent with main flow. Stratton (Stratton, 2014) investigated the effect of coolant flow orientation on the film effectiveness of compound-angle hole. The study compared the performance of SST model, k-ε model and large eddy simulation on reproducing the nature of flow in film hole and conclude that large eddy simulation could capture the detail of flow and unsteady phenomenon correctly.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a higher effectiveness was obtained for the cross-flow directed counter to the spanwise direction of the hole than for the cross-flow directed to the spanwise direction of the hole. Stratton et al [28] investigated the effects of the internal cross-flow on the film cooling performance for a cylindrical hole with a compound angle of 45 • by using RANS models and LES. They found that unsteady vortical structures were formed inside the hole and RANS results did not show a good match to an experimental data while LES predicted the film cooling effectiveness with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%